Epidemiological investigation of allergic rhinitis in children aged 6–12 years in Bayannur City, China - Yan, Xiaobo; Li, Limin (Frontiers in Pediatrics, 2024)
Background: Allergic rhinitis (AR) is an inflammatory condition of the nasal mucosa triggered by exposure to non-harmful substances. Over the past decade, the prevalence of AR in Chinese children has been steadily increasing. However, detailed epidemiological data on AR in children from Bayannur City are lacking.Methods: This study randomly selected six primary schools in Bayannur City. Electronic questionnaires were distributed via the web, and parents and children completed the questionnaires by scanning the two-dimensional code within a designated timeframe. Statistical analysis was performed on the collected data.Results: A total of 4754 valid responses were obtained. The self-reported prevalence of AR among children in Bayannur city was 39.79%. Multivariate analysis revealed that male gender, belonging to an ethnic minority, a history of food or drug allergies, frequent antibiotic use (≥3 times per year in the past two years, with each course lasting ≥3 days), and residence in urban or pastoral areas was associated with an increased prevalence of AR in children. The proportion of children experiencing moderate to severe AR hat impacted their studies or daily life was 48.78%. Chronic AR was reported in 56.71% of cases. Among AR patients with other allergic conditions, the incidence rates were as follows: bronchial asthma 35.99%, upper airway cough syndrome (UACS) 64.32%, secretory otitis media (SOM) 22.41%, obstructive sleep apnea hypopnea-syndrome (OSAHS) 49.58%, allergic dermatitis (AD) 48.72%, and allergic conjunctivitis (AC) 85.20%. The prevalence of AR was 50.30% in urban areas, 13.733% in rural areas and 20.90% in pastoral areas. Seasonal effects on AR prevalence were notably significant in urban and pastoral regions.The prevalence of AR among children in Bayannur city was 39.80%.Of those with AR, 48.72% experienced significant impacts on their learning or daily life, while only 14.80% had no other allergic conditions. There were significant variations in the prevalence and onset of AR among children between urban, agricultural and pastoral areas.